Fiction and Documentation in Suso de Toro’s "Hombre sin nombre" - González Herrán, José Manuel (Madrygal. Revista de Estudios Gallegos, 2015)
Home sen nome is a historical novel set during the Spanish Civil War. This novel is integrated in the process of recovering the “Memoria Histórica” of Spain, an initiative which started in 2006. This work looks into the various documents (bibliographical, hemerographic, testimonial, judicial, etc.) that the author, Suso de Toro, used to build his narrative fiction.
Keywords: Historical Novel; Spanish Civil War; Suso de Toro; Documentation; Narrative Fiction.